"Clean Care for All—It's in Your Hands": The 5 May 2019 World Health Organization SAVE LIVES: Clean Your Hands Campaign. (5th May 2019) - Peters, Alexandra; Borzykowski, Tcheun; Tartari, Ermira; Kilpatrick, Claire; Mai, Safiah Hwai Chuen; Allegranzi, Benedetta; Pittet, Didier
Abstract : Each improvement in infection prevention control contributes toward quality universal health coverage.